Content analysis of gay and lesbian Filipiniana books of the University of the Philippines Diliman library collection - Trinidad, Deoji O. (School of Library and Information Studies, University of the Philippines Diliman, 2011)
The University of the Philippines Library collection has a substantial number of Filipiniana print materials about gays and lesbians. This study use content analysis to analyze the materials' discussion of the eight gay and lesbian issues of self-identity, stereotypes, violence, discrimination, religion, family and relationships, health, and education and career.